Determinants of Intention to Use Sharia Peer-to-Peer Lending: An Extended TAM Approach - Muhammad Lathief Ilhamy Nasution; M. Fauzan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In recent years, financial technology has grown rapidly worldwide, including in Indonesia, where the majority Muslim population has encouraged the development of sharia-based financial services. Despite this growth, research on Islamic financial technology remains limited. This study aims to explore public interest in investment activities that channel capital to micro, small, and medium enterprises through sharia peer-to-peer lending. This research uses a quantitative research design and the technology acceptance model as the theoretical framework. Data were collected from active users of one of Indonesia’s sharia peer-to-peer lending platforms. The research variables include perceived usefulness, perceived ease of use, and religiosity as an extended variable. The findings indicate that perceived ease of use and religiosity positively influence investment interest, whereas perceived usefulness shows no significant effect. These results suggest that user-friendly platform design and alignment with religious values are more critical drivers of investment interest than perceived financial benefits, providing practical implications for Sharia financial technology providers to enhance adoption by focusing on usability and religiosity-based features.